2020
DOI: 10.1101/2020.07.21.214486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep neural network models of sound localization reveal how perception is adapted to real-world environments

Abstract: Mammals localize sounds using information from their two ears. Localization in real-world conditions is challenging, as echoes provide erroneous information, and noises mask parts of target sounds. To better understand real-world localization we equipped a deep neural network with human ears and trained it to localize sounds in a virtual environment. The resulting model localized accurately in realistic conditions with noise and reverberation, outperforming alternative systems that lacked human ears. In simula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 118 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…DNNs provide general-purpose architectures that can be optimized to perform challenging real-world tasks 13 . While DNNs are unlikely to fully achieve optimal performance, they might reveal the effects of optimizing a system under particular constraints 14,15 . Previous work has documented similarities between human and network behavior for neural networks trained on vision or hearing tasks [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…DNNs provide general-purpose architectures that can be optimized to perform challenging real-world tasks 13 . While DNNs are unlikely to fully achieve optimal performance, they might reveal the effects of optimizing a system under particular constraints 14,15 . Previous work has documented similarities between human and network behavior for neural networks trained on vision or hearing tasks [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we set out to discover the efficacy of DNNs as a means to infer proximate mechanisms of audition underlying a targeted auditory phenomena. We modelled binaural hearing (namely, in the context of signal detection), representative of a highly specialized system for which the computations within DNN analogues have barely been examined [11][12][13]. We found that a relatively shallow DNN was able to successfully utilize binaural discrepancies in auditory stimuli, as opposed to seeking an alternative strategy [29] and/or failing to exhibit binaural detection behavior.…”
Section: Deep Neural Network As Analogues Of the Auditory Systemmentioning
confidence: 99%
“…Further, binaural detection is a highly specialised auditory function for which deficits have real-world consequences 25,26 . DNNs may offer the opportunity to bridge this gap between animal and human data, and as yet, the inner workings of DNNs constructed to handle binaural audio have scarcely been considered [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of recent research has pointed out similarities and differences between such deep neural networks and the primate visual system [1,2], but comparable auditory studies remained scarce [3,4]. A new article by Francl and McDermott [5] fills this gap, by revealing how properties of human audition can emerge in deep networks, and how such properties are causally dependent on features of the natural environment.…”
mentioning
confidence: 99%